A gamified mobile health intervention for children in day surgery care: Protocol for a randomized controlled trial. Issue 2 (2nd December 2021) - Rantala, Arja; Vuorinen, Anna‐Leena; Koivisto, Jonna; Similä, Heidi; Helve, Otto; Lahdenne, Pekka; Pikkarainen, Minna; Haljas, Kadri; Pölkki, Tarja
Abstract: Aims: To describe a study protocol for a randomized controlled trial which will evaluate the effectiveness of a gamified mobile health intervention for children in whole day surgery care. Design: A study protocol for a two‐arm randomized controlled trial. Methods: Participants will be randomly assigned to the intervention group ( N  = 62), in which patients receive routine care and play a mobile game designed for children or the control group ( N  = 62), in which patients receive routine care, including a mobile phone application that supports parents during the care path. The primary outcome is children's pre‐operative anxiety, while the secondary outcome measures included fear and postoperative pain, along with parental satisfaction and anxiety. Data collection started in August 2020. Results: The results of the ongoing randomized controlled trial will determine whether the developed gamified mobile health intervention can be recommended for hospital use, and whether it could be used to educate children about their surgical treatment to decrease anxiety.